sRNA scr5239 Involved in Feedback Loop Regulation of Streptomyces coelicolor Central Metabolism - Engel, Franziska; Ossipova, Elena; Jakobsson, Per-Johan; Vockenhuber, Michael-Paul; Suess, Beatrix (Frontiers in Microbiology, 2020)
In contrast to transcriptional regulation, post-transcriptional regulation and the role of small noncoding RNAs (sRNAs) in streptomycetes are not well studied. Here, we focus on the highly conserved sRNA scr5329 in Streptomyces coelicolor. A proteomics approach revealed that the sRNA regulates several metabolic enzymes, among them phosphoenolpyruvate-carboxykinase (PEPCK), a key enzyme of the central carbon metabolism. The sRNA scr5239 represses pepck at the post-transcriptional level and thus modulates the intracellular level of phosphoenolpyruvate (PEP). The expression of scr5239 in turn is dependent on the global transcriptional regulator DasR, thus creating a feedback loop regulation of the central carbon metabolism. By post-transcriptional regulation of PEPCK and in all likelihood other targets, scr5239 adds an additional layer to the DasR regulatory network and provides a tool to control the metabolism dependent on the available carbon source.